Low power reconfigurable receiver architectures for migrating software defined radio technology from base stations to handsets - Vinod Achutavarrier Prasad (2010)
The objective of this research project is to develop low power reconfigurable receiver architectures for migrating Software Defined Radio (SDR) technology from base stations to handsets. We address the issues related to the additional area and power constraints imposed by the resource-constrained handsets, which is a major design challenge in migrating SDR from base stations to handsets.